Effects of removing vitamin and mineral premixes on growth performance and carcass measurements in finishing pigs - Park, J.S.; Gugle, Terry L.; Jones, C.L.; Starkey, C.W.; Lee, D.J.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundreds sixteen pigs were used to determine the effects of deleting vitamin and mineral premixes on growth performance, carcass characteristics, and integrity of vertebrae in finishing pigs housed in large groups with extreme variation in BW. No negative effects on ADG, ADFI, F/G, carcass characteristics, or integrity of vertebrae occurred when the vitamin and mineral premix was deleted.
Keywords: Swine; Finishing pigs; Vitamins; Minerals